An evaluation of the DECS-UP training program for general education supervisors on selected competencies in school health program - Agno, Adelina C.
There is a dearth of local studies done about evaluation of school health training programs in the Department of Education, Culture and Sports (DECS). This is the major reason why this study was undertaken. The work is a quasi-experimental type research. It utilized a "one-group pretest-posttest design". The training program, conducted last September 28 to October 16, 1987 at the University of the Philippines College of Education, Department of Health Education was used as the intervening variable. The subjects were 31 participants, nurses from 8 of the 13 regions of the country. The working hypothesis was that the DECS-UP Inservice Training Program improves the selected competencies (cognitive knowledge, skills, and attitudes) of the General Education Supervisor (GES) in health about school health program. Participant observation and questionnaire were the instruments used in making this study. A take home pre-test was given to the respondents on the first day of the training programs and a take home post-test was given to them a day before the training program ended. Analysis of the data gathered using the T-test statistics favored the rejection of the null hypothesis. The hypothesis that the DECS-UP Inservice Training Program improves the selected competencies of the General Education Supervisors in Health about school health program was accepted. Findings of this research revealed that the preponderant educational qualification of the General Education Supervisors (GES) were a masteral degree in health education and master of arts units in the same field. Planning, communication, teamwork, health assessment, and health education were the first five topics that the respondents perceived they needed training in order to maximize effectivity in their work. Malnutrition ranked as the number 1 crucial health problem in the school/community where the respondents came from, followed by communicable diseases, environmental pollution, drug dependence, and accidents. T-test statistics between the pre-test and the post-test scores on the contents of the training program revealed a significant result at 0.05 level. With regards to the training program objectives, the respondents maintained that these were "much attained". These conclusions could be drawn from the findings of this study: (1) that the DECS-UP Training Program improved the selected competencies of the General Education Supervisors in Health in the school health program and, 2) that evaluation of a training program is important to justify its effectiveness.